1992
DOI: 10.1136/jcp.45.8.731
|View full text |Cite
|
Sign up to set email alerts
|

Pseudohyperphosphataemia in patients with multiple myeloma.

Abstract: The phosphate concentrations were measured in 41 patients who had multiple myeloma with paraproteinaemia using four different methods to compare the incidence of pseudohyperphosphataemia. The direct acid/molybdate method produced the highest number of anomalous results. The erroneously high phosphate concentration was attributable to the presence of turbidity in the reaction mixture. No association was found between paraprotein type and occurrence of turbidity. The This is an enzymatic method in which the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…In previous reports where a series of patient samples was investigated, different criteria for pseudohyperphosphataemia were used, 6,9,11,12 and this may explain the variable incidence (8-49%) of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports where a series of patient samples was investigated, different criteria for pseudohyperphosphataemia were used, 6,9,11,12 and this may explain the variable incidence (8-49%) of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of the complex is pH dependent and uses an acid buffer (3,7 ). The low pH environment of the reaction mixture can lead to precipitation of immunoglobulins and result in increased turbidity and light scattering (5,7 ). Resolution of the interference is obtained by diluting the sample or removing the plasma proteins via various deproteinization methods (5, 7 ).…”
Section: Immunoglobulin Excess Affecting Measurement Of Phosphorousmentioning
confidence: 99%
“…Absorbance of the unreduced phosphomolybdate complex is measured and indexed to a calibration curve to determine analyte concentration (3,7 ). The formation of the complex is pH dependent and uses an acid buffer (3,7 ). The low pH environment of the reaction mixture can lead to precipitation of immunoglobulins and result in increased turbidity and light scattering (5,7 ).…”
Section: Immunoglobulin Excess Affecting Measurement Of Phosphorousmentioning
confidence: 99%
See 1 more Smart Citation
“…or by the removal of protein, either by pretreatment of the samples or by using an analyser which incorporates a dialysis step. 3,5,7,8,[10][11][12] Correspondence: Dr Shirley A Bowles. examination of the reaction mixture in a number of studies has indicated that significant turbidity occurs in some cases of paraproteinaemia.s-v'I-P The precipitates produced in this way have been shown to contain the monoclonal immunoglobulin present in the unprocessed serum.…”
mentioning
confidence: 99%